Attitude towards Life as a Bioethical Challenge - Cifrić, Ivan (Array, 2010)
Attitude towards life is one of the most important question concerning bioethical issues in contemporary society. In this paper we are mostly analyzing relation to human life, with few issues that concerns animal life as well as human. Relation to life is conceptualized through acceptance (or no acceptance) of abortion, suicide, euthanasia, human cloning and cloning for medical purposes, producing of GMF and using of animals in medical experiments. Abortion is one of indicators which implied on questionable bioethical discussions in contemporary society. It is an indicator of social and personal relation toward unborn life. Two basic attitudes and their own arguments are showed in the contemporary discourse. First attitude is allowing (pro) abortion in certain cases, such as heavily damage of the fetus, when woman is not married, when married couple doesn’t want any more children and when economic situation is not good. The other one is contra abortion. The arguments for this attitude are also different, for example: because abortion is a crime and unmoral act, because it endangers woman’s life and also endangers demographic survival of the nation. The question is who should decide about these issues? According to ones abortion should be legally regulated, regardless if it is complete forbidden or partially allowed, and according to others legal abortion regulation is not necessary, but it should be allowed woman to decide. Results of the empirical research (survey) from the project “Religious Changes in Croatia” (Institute for Social Researches, Zagreb) will be presented in this paper. Survey is conducted on the representative sample (N=2220, Year 2004), and for perception of abortion special instrument with ten statements is applied, while other bioethical issues are covered with one statement. The main goal of this paper is to present relation between examinee’s opinions about abortion, suicide, euthanasia, human cloning and cloning for medical purposes, producing of GMF and using of animals in medical experiments and religiosity, relation toward life after death and some socio-demographic characteristics.